Land capital in agriculture: peculiarities of assessment and formation - Dorosh, Y.; Shkuratov, O.; Tarnopolskyi, A. (Land Management, Cadastre and Land Monitoring, 2020)
The article identifies that land resources are not only the basis for the allocation of productive forces and the main means of production in agriculture, but also serve as an effective element of investment capital of agricultural enterprises – land capital. It is determined that in the existing institutional conditions, land resources do not create capital in agricultural production, which requires justification of mechanisms for involving them in economic circulation in order to provide investment support to the agricultural sector of the economy. This increases the importance of the development of theoretical and methodological foundations for the assessment and formation of land capital in Ukrainian agriculture.It is established that one of the key factors for the capitalization of agricultural lands is their objective assessment, which corresponds to the current economic conditions and reveals them as a source of capitalized income. Based on studies of the relationship between rental payments and land valuation, a disparity of these indicators has been identified in the majority of regions in Ukraine. As a result, the application of normative monetary valuation for determination of the value of land capital has been proven biased.It is determined that one of the ways of estimation and formation of land capital in agriculture, under the conditions of institutionally restricted regime of the law of supply and demand, is the capitalization of leased land. In this case, the value of land capital can be calculated as the product of the average annual rent for the land and the period of its capitalization. A promising area of research in the context of the analysis is to substantiate the process of transferring agricultural land to the balance sheet of the enterprise at the cost of capitalized rental payments.